Metode Omnibus Law Sebagai Upaya dalam Mengatasi Hyper Regulation di Bidang Perekonomian - Alsyam, Alsyam (Universitas Ekasakti, 2023)
In Indonesia, the understanding of rule of law cannot be separated from the influence of the development of good thinking fromrule of law northe rule of law, but still has distinctive characteristics as shown in the 1945 Constitution of the Republic of Indonesia. The method for forming laws and regulations in Indonesia uses codification and sectoral. The codification method is the preparation of legal regulations in a book of laws in writing including collecting scattered legal provisions, then arranged systematically. There are various problems that arise in the formation of legislation in Indonesiaover regulations, overlapping regulations, multiple interpretations, ineffective, and sociologically problematic. Government encouragement in the progress of the Indonesian economy through the application of the methodlaw to all namely the Job Creation Law. This research is a legal research (doctrinal research) with a conceptual approach (conceptual approach) and the legal approach (statues approach). The results of this study explain that MethodAll Law in the formation of laws and regulations it has been regulated through Law Number 13 of 2022 where the purpose of the Omnibus Law is to link a rule with other related rules as intended to be integrated. Second, the Omnibus Law as an effort to overcome hyper regulation as a whole. Simplification as to avoid overlapping between regulations and other regulations